The Influence of Creativity and Digital Literacy on Entrepreneurial Readiness Among Culinary Phase F Students at SMK Negeri 6 Padang - Agustina Agustina; Widia Astuti; Detman Detman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine how much: (1) the influence of creativity on the entrepreneurial readiness of Culinary Phase F Students at SMK Negeri 6 Padang (2) the influence of digital literacy on the entrepreneurial readiness of Culinary Phase F Students at SMK Negeri 6 Padang, (3) the influence of creativity and digital literacy on the entrepreneurial readiness of Culinary Phase F Students at SMK Negeri 6 Padang. This study was conducted at SMK Negeri 6 Padang, the method used in the study was a quantitative method with data collection techniques through distributing questionnaires to respondents. Respondents in this study were Culinary phase F students at SMK Negeri 6 Padang. The population in this study was 106 culinary students of phase F with a sample size of 84 students. Sampling in this study used proportional random sampling or random sampling. The data collection technique used a questionnaire then analyzed using multiple linear regression with the help of SPSS version 25 and the hypothesis was tested using the t test and F test. The results of this study indicate that (1) the influence of creativity has a positive and significant effect on the entrepreneurial readiness of culinary students of phase F at SMK Negeri 6 Padang with a t-value of 3.708 ˃ 1.980 with a significance level of 0.000 less than 0.05. (2) There is a positive and significant influence of digital literacy on entrepreneurial readiness with a t-value of 7.732 ˃ from 1.980 with a significance level of 0.020 <0.05. (3) There is a simultaneous influence of creativity and digital literacy on the entrepreneurial readiness of culinary students of F phase at SMK Negeri 6 Padang, with the obtained F count ˃ F table value of 149.874 ˃ 3.908 and significant at 0.000 < 0.05.